2017
DOI: 10.2337/db16-1592
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Adam et al. Metformin Effect on Nontargeted Metabolite Profiles in Patients With Type 2 Diabetes and in Multiple Murine Tissues. Diabetes 2016;65:3776–3785

Abstract: We read with interest the recent article by Adam et al. (1) suggesting an action of metformin on citrulline metabolism in patients with type 2 diabetes. This study provides compelling evidence that metformin treatment is associated with a decrease in plasma citrulline in these patients and also in multiple tissues in diabetic mice. The authors speculate that high citrulline may be associated with insulin resistance, and the accompanying commentary (2) questioned whether a metformin-mediated decrease in citru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Is metformin's beneficial effect on insulin sensitivity mediated not only by inhibiting gluconeogenesis (5) but also by its effect on the nitric oxide cycle (3) and the consequent alteration of citrulline concentrations? We therefore support the suggestion by Jegatheesan et al (1) to investigate the interaction of citrulline and metformin. Clinical studies to investigate the specific role of citrulline in T2D and its potential treatment benefits as a supplement to metformin are highly promising.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Is metformin's beneficial effect on insulin sensitivity mediated not only by inhibiting gluconeogenesis (5) but also by its effect on the nitric oxide cycle (3) and the consequent alteration of citrulline concentrations? We therefore support the suggestion by Jegatheesan et al (1) to investigate the interaction of citrulline and metformin. Clinical studies to investigate the specific role of citrulline in T2D and its potential treatment benefits as a supplement to metformin are highly promising.…”
supporting
confidence: 92%
“…We advise caution with the statement by Jegatheesan et al (1) that "the liver does not play any significant role in these interorgan exchanges because liver citrulline is almost exclusively synthesized locally and channeled into the urea cycle." It has been shown that citrulline can be taken up by the liver from the blood (4).…”
mentioning
confidence: 86%
See 1 more Smart Citation